Assessment of Wnt-5a, Anti-SMA, FGF-23, and Anti-CCP Biomarkers in Patients with Rheumatoid Arthritis - Marouf, Bahramand Babatahir; Amin, Kawa; Rahman, Heshu Sulaiman (Sulaimani Journal for Pure and Applied Sciences, 2023)
Background: Rheumatoid arthritis (RA) is a multifactorial autoimmune disease with unknown etiology that mainly affects synovial joints Objectives: To compare the level of serum biomarkers (Wnt5a, anti-SMA, FGF23, and anti-CCP) in RA patients and healthy control. Methodology: This case-control study was conducted on 88 patients with RA and 88 normal healthy individuals at the Rheumatology Center, Sulaimaniyah, from November 2021 to November 2022. A detailed questionnaire for the collection of sociodemographic measures was filled out for each participant. Then, the levels of Wnt5a, anti-SMA, FGF23, and anti-CCP were determined using the ELISA technique. Results: The patients reported higher levels of ESR and CRP than healthy controls. Most patients (63.7%) had moderate disease activity concerning DAS-28. There was a highly significant difference (p<0.001) between patients’ serum Wnt5a, FGF23, and anti-CCP levels compared to healthy controls except for anti-SMA. Additionally, there was a significant correlation between Wnt5a and FGF23 (p<0.001); Wnt5a and anti-SMA (p<0.001); FGF23 and anti-SMA (p<0.001). Finally, no correlation between the DAS-28 score and biomarkers was seen in RA patients. Conclusions: There was no significant correlation in the patient’s serum Wnt5a, FGF23, anti-SMA, and anti-CCP with different age groups, duration of RA and joint involvements.
Keywords: Rheumatoid arthritis; serum biomarkers; case control study; autoimmune disease